2020
DOI: 10.1002/jmv.26215
|View full text |Cite
|
Sign up to set email alerts
|

Eighteen‐year follow‐up cohort study on hepatitis B and C virus infections related long‐term prognosis among hemodialysis patients in Hiroshima

Abstract: This study aimed to investigate the prevalence trend of hepatitis B virus (HBV) and hepatitis C virus (HCV) infections and their genotype distribution among hemodialysis patients, determining their long‐term prognosis and the risk factors to the mortality. This cohort study used both the medical data and the blood samples of hemodialysis patients at nine dialysis centers in Hiroshima from 1999 to 2017. Hepatitis B surface antigen (HBsAg) and anti‐HCV were screened and then amplification was done to positive se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…At times, HCV genotype 2b comes across over genotype 1b among those born after 1970 while genotype 2a is constantly found in all age groups in Japan (8,9,11). A similar pattern of genotype distribution was also found in hemodialysis patients and a change in genotype distribution from genotype 1b to 2a/2b was also reported among those who started dialysis after 1991 (12). In this review article, we would like to express the epidemiology of HCV in Japan.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…At times, HCV genotype 2b comes across over genotype 1b among those born after 1970 while genotype 2a is constantly found in all age groups in Japan (8,9,11). A similar pattern of genotype distribution was also found in hemodialysis patients and a change in genotype distribution from genotype 1b to 2a/2b was also reported among those who started dialysis after 1991 (12). In this review article, we would like to express the epidemiology of HCV in Japan.…”
Section: Introductionmentioning
confidence: 76%
“…The annual incidence of HCV infection was 0.33% i.e., 3 in 1,000 hemodialysis patients were newly infected with HCV infection in a year. A recent study showed that the decreasing trend of both anti-HCV and HCV RNA positivity was found by their dialysis started year (12). For those who started dialysis after 2002, anti-HCV prevalence was 9.5% and HCV RNA positivity was 7%.…”
Section: Hcv Infection Among Hemodialysis Patientsmentioning
confidence: 99%
“…The genotype distribution patterns in such cases usually reflect the distribution in the general population (Ko et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Reports on other HCV 3 subtypes causing chronic hepatitis or dialysis‐related infections exist; however, HCV 3f‐related outbreaks could not be retrieved from published literature. Multiple reports on the dialysis‐related transmission of HCV genotypes such as 1b, 1a, and 3a, exist (Hmaied et al, 2006; Izopet et al, 1999; Ko et al, 2020). Recently, a Pune (India)‐based study reported an HCV outbreak in a dialysis unit, where 84.6% of the isolates belonged to HCV 1b with 99.3% nucleotide sequence similarity, indicating a nosocomial transmission (Roy et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation